Uses of media and Information and Communication Technologies in education and training since 1960 to 2006. Case of Togo - (:unkn) unknown (My University, 2007)
From the sixties to the eighties, the potentialities of using radio and television in education and training were thoroughly explored. These investigations have raised and entertained promising discourses and great hopes among educators regarding the possible improvement pf pedagogical practices and the widening of access to an increasing number of individuals. In the face of pressing needs for education and training, Francophone Western Africa has witnessed the development and implementation of radio and television –based education programs in contexts which were unfamiliar with such usage. This heralded the rapid petering out of related efforts, especially in the face of mounting and sustained resistance and pressure from parents and teachers and the related management difficulties concerning such “experiments”. However, the advent of ICTs in the nineties and the increasingly obvious potential for online and distance education and training as well as the governance of the education system, especially regarding quality assurance possibilities have brought in their wake a revival of similar hopes and discourses. As in the past, several initiatives were undertaken to introduce ICTs in education and training. Several questions are thereby raised. In the first instance, the question arises whether earlier lessons regarding the use of radio and television have been learnt. In addition, what could be the real and effective contribution of ICTs in education and training in the context of African countries given the current state of their educational systems, especially how could ICTs respond partially to the high demand for quality education linked to its exponential demographic expansion? Grounded in case studies of experiments in the use of media and ICTs in education and training in Francophone West Africa, especialy in Togo, this thesis hopes to shed informed light on potential solutions tha
Keywords: African Research